IMPLEMENTATION TAX DIGITAL OF CONTENT CREATOR ON TIKTOK SOCIAL MEDIA - Christian Gunawan; Dian Purnama Sari (JOURNAL OF ACCOUNTING, ENTREPRENEURSHIP AND FINANCIAL TECHNOLOGY (JAEF), 2023)
This study aims to determine the application of digital tax on the TikTok platform. This research is qualitative research involving several informants, such as TikTok content creators, TikTok agencies, and tax consultants. This study uses data analysis techniques. The results of this study indicate that content creators are subject to income tax by being treated as freelancers. TikTok content creators can use a calculation norm of 50% to calculate their net income. Their income has been deducted by TikTok, but does not include taxes. The agency also does not collect income tax on TikTok content creators, so there has been no implementation of digital taxes on the TikTok platform. Therefore, content creators on the TikTok platform must carry out their own tax. While carrying out their own tax, content creators experience several difficulties, such as difficulty in understanding complex tax regulations.